Efforts to Improve Junior High School Students’ Learning Motivation through the Implementation of Ice Breaking in Islamic Religious Education Learning - Iftisa Oktika Sari; Azizah Aryati (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Learning motivation is a crucial factor influencing students’ academic success, particularly in Islamic Religious Education, which is often perceived as monotonous. Low learning motivation among seventh-grade students at SMP Negeri 32 Satu Atap Kaur highlights the need for innovative instructional strategies to create an engaging learning environment. Objective: This study aims to examine the effect of icebreaking activities on improving students’ learning motivation in Islamic Religious Education subjects. Method: The research employed Classroom Action Research (CAR) across two cycles. Data were collected using learning motivation questionnaires and classroom observations. Result: The average student motivation score in the pre-cycle stage was 60.5, with classical completeness reaching only 30%. After implementing icebreaking activities in Cycle I, the average score increased to 68.7, with classical completeness improving to 60%. In Cycle II, the use of more varied, interactive icebreaking activities further increased the average motivation score to 80.2, with classical completeness reaching 90%. These findings demonstrate that icebreaking activities are effective in enhancing students’ learning motivation, fostering a positive classroom atmosphere, and encouraging active participation. Conclusion: Regular integration of icebreaking activities can significantly improve student motivation in Islamic Religious Education. Contribution: This study provides practical insights for teachers on implementing innovative, student-centered learning strategies.